2017
DOI: 10.22146/agritech.17002
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Mikrobiologis dan Kimiawi Kefir Susu Kambing dengan Penambahan Lactobacillus acidophilus FNCC 0051 dan Tepung Kulit Pisang Kepok (Musa Paradisiaca)

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penambahan tepung kulit pisang dan Lactobacillus acidophilus FNCC 0051 terhadap kualitas mikrobiologis dan kimiawi kefir susu kambing. Kefir dibuat dari susu kambing dengan kefir grain 3 % (w/v) dan Lactobacillus acidophilus FNCC 0051 (0, 1 dan 3 % (v/v)) serta tepung kulit pisang (0, 1 dan 2 % (w/v)). Semua perlakuan diinkubasi pada suhu ruang (± 28,5 °C) selama 10 jam, hingga pH turun menjadi 4,2 sampai 4,6. Uji kualitas kefir yang diamati yaitu mikro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
2
1
0
3
Order By: Relevance
“…This is in line with previous research by [37] where symbiotic yogurt with the addition of prebiotics in the form of 2% inulin can increase the viability of probiotics. Similar results were also shown in previous studies by [27] showing that the addition of banana peel flour to goat's milk kefir provides high probiotic viability. According to [38] the requirement for probiotic drinks contains more than 10 8 or 8 logs of probiotic bacterial cells per millilitre in a live state.…”
Section: Lactic Acid Bacteria Viabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with previous research by [37] where symbiotic yogurt with the addition of prebiotics in the form of 2% inulin can increase the viability of probiotics. Similar results were also shown in previous studies by [27] showing that the addition of banana peel flour to goat's milk kefir provides high probiotic viability. According to [38] the requirement for probiotic drinks contains more than 10 8 or 8 logs of probiotic bacterial cells per millilitre in a live state.…”
Section: Lactic Acid Bacteria Viabilitysupporting
confidence: 91%
“…In the study of [26] where the increase in total LAB in probiotic ice cream occurred due to the high crude fibre and starch content in banana peel flour so that Lactobacillus casei could be used to grow. The same thing was also found in the research of [27] where the activity of lactic acid bacteria increased with the addition of banana peel flour which showed the role of fructose oligosaccharides used by Lactobacillus acidophilus as a source of nutrition.…”
Section: Total Lactic Acid Bacteriasupporting
confidence: 75%
“…Terdapat juga minuman yoghurt yaitu minuman fermentasi semi padat yang dibuat dari susu dengan penambahan bakteri Streptococcus thermophillus dan Lactobacillus delbruecki sub sp, bulgaricus. Sedangkan pada kefir adalah minuman yang menghasilkan asam dan alkohol yang berasal dari bakteri asam laktat dan khamir yang selama proses fermentasi (Martharini & Indratiningsih, 2017).Bahan baku kefir adalah dari susu yang ditambahkan stater kefir grain yang difermentasi selama 24 jam. Dengan berkembangnya teknologi yang ada yoghurt berasal dari nabati yaitu kedelai, jagung, sari kulit nanas, ekstrak cincau hijau, sari kurma, buah naga merah (Rizal et al, 2016).…”
Section: ) Produk Minumanunclassified
“…The color of goat's milk kefir is influenced by the fat and solid content in the milk is by research by Mandang et al (2016). Martharini and Indratiningsih (2017) suggested that higher content of Lactobacillus acidophilus FNCC 0051 decreased the fat contained in milk due to the development of lactic acid bacteria during the fermentation process which produces lipase enzymes to break down fat. Kinteki et al (2018) observed that the longer the fermentation, the higher the color aspect assessment from the panelists for goat milk kefir.…”
Section: Kefirmentioning
confidence: 99%